Papillary Thyroid Carcinoma in a Toxic Adenoma - Lamberg, B.-A.; Mäkinen, J.; Murtomaa, M. (Nuklearmedizin - NuclearMedicine, 1976)
A patient with a well differentiated papillary carcinoma within a toxic adenoma is reported. Only a few similar cases have been recorded in the literature. A common origin of both lesions is suggested.